The Urgency of Regulating Priority Rights for Former Land Rights Holders Over Management Rights - Maratul Muslimatus Salimah; Imam Koeswahyono; Bambang Eko Supriyadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Regulations regarding management rights are still considered sporadic and fragmented, making the substance of management rights difficult to understand. One of the authorities of the holder of management rights is to use and utilize all or part of the land with management rights for their own use or in collaboration with third parties through land utilization agreements. Third parties can utilize the part of the land that is collaborated with the right to cultivate, right to build, or right to use. As is known, land rights can be granted over state land and management rights. If the term of land rights over state land expires, the former holder of the land rights is given priority rights to extend the land rights. This is different from land rights over management rights, where currently there are no regulations regarding the granting of priority rights to former rights holders. Third parties who utilize land with management rights properly and in accordance with spatial plans should be given priority rights to extend the land rights over management rights. This type of research is normative legal research with a statutory regulatory approach, a case approach, a conceptual approach, and a historical approach. The results of this study indicate that there is an urgency to regulate the priority rights of former holders of land rights over management rights, considering that the substance of management rights is part of the state's right to control. Thus, the characteristics of management rights in the context of land use agreements by third parties are in line with the objectives of the state's right to control, namely for the greatest prosperity of the people.